2009
DOI: 10.1158/1535-7163.mct-09-0463
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibition of Wee1 kinase by MK-1775 selectively sensitizes p53-deficient tumor cells to DNA-damaging agents

Abstract: Wee1 is a tyrosine kinase that phosphorylates and inactivates CDC2 and is involved in G 2 checkpoint signaling. Because p53 is a key regulator in the G 1 checkpoint, p53-deficient tumors rely only on the G 2 checkpoint after DNA damage. Hence, such tumors are selectively sensitized to DNA-damaging agents by Wee1 inhibition. Here, we report the discovery of a potent and selective smallmolecule inhibitor of Wee1 kinase, MK-1775. This compound inhibits phosphorylation of CDC2 at Tyr15 (CDC2Y15), a direct substrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
509
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(530 citation statements)
references
References 28 publications
17
509
4
Order By: Relevance
“…The consensus view is that Wee1 inhibition facilitates tumor cell killing through G 2 /M checkpoint inactivation, which would catalyze mitotic catastrophe (23)(24)(25). As expected, Wee1 inhibition is synergistic with DNA-damaging agents, specifically in TP53-mutant cancer cell lines (3). However, a recent study indicated that only a subset of TP53-mutant patient-derived pancreatic cancer xenografts showed benefit from Wee1 inhibition (21).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The consensus view is that Wee1 inhibition facilitates tumor cell killing through G 2 /M checkpoint inactivation, which would catalyze mitotic catastrophe (23)(24)(25). As expected, Wee1 inhibition is synergistic with DNA-damaging agents, specifically in TP53-mutant cancer cell lines (3). However, a recent study indicated that only a subset of TP53-mutant patient-derived pancreatic cancer xenografts showed benefit from Wee1 inhibition (21).…”
mentioning
confidence: 77%
“…Chemical inhibitors for several cell cycle checkpoint kinases have been developed. Preclinical research, however, has shown that the efficacy of therapeutic checkpoint inhibition is context-sensitive and depends on the genetic make-up of an individual cancer (2,3). Therefore, to optimally implement such novel inhibitors in the clinic, the molecular characteristics that determine inhibitor activity need to be identified to select eligible patients and to anticipate on mechanisms of acquired resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Subsequently it was reported that treatment with the clinical Wee1 inhibitor MK-1775 (AZD-1775) likewise had striking cytokinetic effects, including features suggestive of premature entry into mitosis during early S-phase. 19,20 Of the Wee1 inhibitors, MK-1775 is currently the most advanced in clinical development, and it is reported to be highly selective toward Wee1 (21). As a single agent it appears to be well tolerated, but has little anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Because p53 activation potently enforces the G 1 /S checkpoint, it has been theorized that p53-null tumors are especially dependent on the S and G 2 /M checkpoints to maintain genomic integrity. Therefore, inhibitors of cell cycle checkpoint proteins have largely been developed for the treatment of p53-deficient malignancies (5,21,24,47,48). Meanwhile, MDM2 i s have been developed for use in p53-sufficient malignancies because they have little or no impact in the absence of p53.…”
Section: Discussionmentioning
confidence: 99%